Complete mitochondrial genome of vulnerable fighting fish Betta coccina (Actinoptergii: Perciformes: Osphronemidae) with phylogenetic consideration - Yusof, Muhammad Fitri; Zainon, Zarick; Jaapar, Muhamad Zudaidy; Amatul-Samahah, Md. Ali; Mohamad, Mohd Azrul Naim; Faisal, Adriana Batrisyia Mohd; Han, Ming Gan (Academia Journal of Biology, 2024)
We reported the first complete mitochondrial genome of the Scarlet Fighting Fish, Betta coccina (Vierke, 1979), a species of concern due to its vulnerable status. Genome skimming was performed on a specimen collected from Johor, Malaysia to recover its mitochondrial genome. The assembled complete mitogenome is 16,502 bp in size, comprising the standard set of 13 protein-coding genes, 22 tRNAs, and two rRNAs, typical of most vertebrates mitogenome. Phylogenetic analysis was conducted using the whole mitogenome of B. coccina and four publicly available mitogenomes of Betta spp. Our analysis revealed that the B. coccina currently occupied a basal position relative to other Betta spp. with maximal support value. Our results provide valuable insights for both evolutionary studies and genetic conservation efforts of B. coccina and its related species.